Telaah Kritis Hukum Perkawinan Islam Perspektif Hukum Positif Di Indonesia - Mudaí, Syaiful; Maghfiroh, Devi Nur (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2021)
Marriage is an inner and outer bond between two different people, namely a man and a woman. Therefore, marriage creates privileges and consequences that are only obtained when the marriage has taken place. In Indonesia, there are three products of legislation that specifically regulate marriage issues. Not only regulating marriage, furthermore, the substance regulates all issues related to marriage, starting from matters related to the pre-marital period such as the terms of marriage, the marriage period lasts such as the rights and obligations of husband and wife, until the post-marital period has broken up such as separation. wealth. The three products of these regulations are: the Civil Code or Burgelijk Wetboek, the 1974 Law on Marriage, and the Compilation of Islamic Law. All three as positive laws in Indonesia are a means of regulating marriage for the people of Indonesia.